Pengaruh Kualitas User Interface, Ketersediaan Produk, Dan Ketepatan Estimasi Pengiriman Terhadap Loyalitas Pengguna Shopee (Studi Kasus Pada Gen Z Di Kota Malang) - Sari, Ridah Anjar; Susyanti, Jeni; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The rapid development of e-commerce in Indonesia, particularly among Generation Z, presents both challenges and opportunities for platforms like Shopee. In this context, User Interface quality, product availability, and delivery estimation accuracy are critical factors that can significantly influence user loyalty. This research aims to analyze the impact of these three variables on user loyalty to Shopee in Malang City. A quantitative approach was employed, utilizing a survey involving 80 randomly selected respondents. Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression to examine the relationships between the variables. The results indicate that User Interface quality and product availability significantly enhance user loyalty, while delivery estimation accuracy does not show a significant effect. These findings emphasize that a positive user experience, characterized by an appealing interface and sufficient product availability, can effectively boost loyalty to Shopee. This study offers valuable insights for Shopee managers to refine marketing strategies and improve user experience. By prioritizing enhancements in User Interface quality and product availability, it is anticipated that user loyalty among Generation Z will increase substantially. The research also recommends further studies to explore additional factors influencing user loyalty on e-commerce platforms, including customer service quality and promotional strategies. Keywords : User Interface quality, product availability, delivery estimation accuracy, user loyalty, Shopee, Generation Z